Heart rate variability, training variation and performance in elite swimmers - Atlaoui, D.; Pichot, V.; Lacoste, L.; Barale, F.; Lacour, J.-R.; Chatard, J. C. (International Journal of Sports Medicine, 2007)
The aim of the present study was to investigate the relationships between heart rate variability (HRV) changes and both training variations and performances in elite swimmers. A secondary purpose was to measure catecholamine urinary excretion in elite swimmers to validate the HRV indices of sympathetic activity during training. Thirteen swimmers (4 females and 9 males) were tested before and after 4 weeks of intense training (IT) and 3 weeks of reduced training (RT). At the end of each period, the swimmers participated in an official competition of their best event. Individual performances were expressed as percentage of the previous season's best performance. Spectral analysis was used to investigate RR interval variability. HRV indices failed to show any significant changes between the study periods (p > 0.05). Pre-IT HF was correlated with performance (r = 0.45; p = 0.05) and HFnu (r = 0.59; p < 0.05) during RT. On the other hand, once RT was completed, HFnu was correlated positively to performance (r = 0.81; p < 0.01) and negatively to fatigue (r = - 0.63; p < 0.03). Conversely, the indices of sympathetic activity, i.e., LFnu and LF/HF ratio were inversely related to performance (both r = - 0.81; p < 0.01); total fatigue score was correlated to the changes in HFnu (r = - 0.63; p < 0.03) and in the LF/HF ratio (r = 0.58; p < 0.05). Changes in the adrenaline/noradrenaline ratio over the follow-up period were related to the changes in the LF/HF ratio (r = 0.45; p < 0.03). In highly trained swimmers coping well with a training program, including 4 weeks of IT followed by 3 weeks of RT, HRV indices were unaltered. On the other hand, after the 3 weeks of RT, HFnu was positively related to performance and inversely related to the fatigue score. Thus, elevated initial HF levels could be important in the parasympathetic activity increases during taper and, hence, in swimming performance improvement.